Analysis of the development of renewable energy resources in the transcarpathian region in the context of balanced development of territorial communities - Pop, S.; Peresoliak, V.; Sharodi І. (Land Management, Cadastre and Land Monitoring, 2025)
Abstract. This article analyzes the current state of the potential of renewable energy resources in the Transcarpathian region. The main problems of the use of renewable energy resources by territorial communities of the region are identified and the main problems that hinder the construction of new renewable energy (RE) facilities are clarified. In order to determine the strategic directions of development of balanced environmental management of territorial communities and the prospects for the development of renewable energy resources of Transcarpathian region, up-to-date information on the development of the unique potential of renewable energy resources (RER) is updated as of mid-2024. Taking into account the inexpediency of resuming the operation of the Burshtynska TPP, which provided the energy needs of Transcarpathia, the prospects and importance of accelerating the achievement of the goals of self-energy supply of Transcarpathia and sustainable development in the long term by activating the development of the existing unique RE potential are considered. Given the significant destruction of the Unified Energy System (UES) facilities by the Russian occupiers, on 13 of August 2024, the government approved the National Action Plan for Renewable Energy until 2030, which provides for accelerating the diversification, decarbonization, decentralization and security of the Unified Energy System, commissioning 24 GW of green energy generating capacities, and achieving a 27% share of its share in total electricity consumption. This requires the construction of 6,1 GW of wind power, 12,2 GW of solar power, 4,7 GW of hydropower, 876 MW of bioenergy, and 40 MW of geothermal energy. In the current realities of martial law, this must be done quickly, reliably, and rationally in terms of financial costs and environmental protection. Therefore, to achieve the above indicators, it is important to develop available renewable energy resources (RER) in all regions of Ukraine, which, due to their spatial distribution and proximity to consumers, will strengthen the stability of the unified energy system (UES). Key words: green energy, geothermal energy, solar energy, small hydropower, wind energy, ecology, sustainable development of territories, decarbonization, energy self-sufficiency.